Crescimento de arundina graminifolia (D. Don.) hochr. Em diferentes meios de cultivo e níveis de pH - Pedroso-De-moraes, Cristiano; Souza-Leal, Thiago [UNESP]; Diogo, José Alberto; Canabrava, Rosangela Isete; Pedro, Natália Pierobon; Marteline, Marco Aurélio [UNESP] (Centro Universitario de Maringa, 2017)
Arundina graminifolia is an orchid, widely appreciated for its beauty, also used as medicine. Low investments in the improvement of current in vitro culture techniques, an important tool for the propagation of species of orchids, impairs decrease in costs. Current analysis assesses the effects of culture medium 1/2MS and two media based on commercial fertilizers Hyponex® (NPK 6.5-6-19) and Kristalon orange® (NPK 6-12-36), at three pH levels (5.3, 5.8 and 6.3), on the in vitro growth of A. graminifolia. Seeds were placed in four flasks with each medium and 20 seedlings were removed randomly after 180 days of culture from each flask, for statistical analysis. The most efficient culture medium was 1/2MS at pH level 5.8, with the greatest media for all variables analyzed.
Growth of arundina graminifolia (D. Don.) hochr. In different culture media with different pH levels
Keywords: Arundina bambusifolia; Bamboo orchid; In vitro propagation; Orchidaceae